Social structuring and social network analysis (SNA): religion and the God node - Oliva, Miguel (AWARI, 2020)
This article links the theory of social structuring and the SNA (Social Network Analysis). We understand the emergence of religious networks as a more general process of social structuring. In the processes of structuring social networks, the connections are no longer random and become hierarchical and preferential links. Social structuring is associated with the models of random networks (ER); the greater or lesser degree of structuring, is a greater or lesser degree of randomness in the structuring of social ties. The concepts of real and potential connections are addressed, and ARS models are applied to the characterization of monotheism and polytheism. The nature of religious ties and normative networks is specified. Isomorphism of social structuring in politics and religion, and inter-religious conflict, are addressed.